E-048 Predictive factors of good outcomes in patients with acute basilar artery occlusion after endovascular treatment. (4th August 2020) - Ha, S
Abstract : Background and Purpose: Basilar artery occlusion (BAO) is associated with high risk of disability and mortality. The objective of this study was to investigate prognostic factors in patients with acute basilar artery occlusion treated with mechanical thrombectomy, focusing on collateral status and recanalization time from symptom onset. Methods: All eligible patients from January 2012 to October 2019 undergoing endovascular treatment (EVT) due to acute BAO were retrospectively reviewed. The baseline posterior circulation collateral status was assessed with Basilar Artery on Computed Tomography Angiography (BATMAN) score and Posterior Circulation Collateral Score (PC-CS). Good outcome was defined as a modified Rankin scale score of ≤2 at 3 months and successful recanalization as thrombolysis in cerebral infarction (TICI) grade 2b or 3. The association between baseline and clinical parameters including and favorable outcome was evaluated with logistic regression. Results: Our sample included a total of 81 eligible patients (49 males, mean age 70.3 years) with a median baseline and discharge National Institute of Health Stroke Scale (NIHSS) score of 12. Patients with good clinical outcome showed a lower baseline National Institute of Health Stroke Scale (NIHSS) score, a more proportion of distal BAO, and a higher BATMAM and PC-CS (p<0.001). According to the analysis subdivided of patients within and over 6 or 12 hours, the time from symptom onset to recanalization was no correlation with good outcome. Multivariable logistic analysis showed Baseline NIHSS <15 (odds ratio [OR] 8.49 95% confidence interval [CI]: 2.01–35.82, P =0.004), PC-CS ≥ 6 (OR 3.79 95% CI: 1.05–13.66, P =0.042) and distal BAO (OR 3.67 95% CI: 1.10–12.26, P =0.035) were independent predictors of good clinical outcomes. Conclusion: This study suggested that good collateral circulation and distal BAO are independent predictors of clinical outcome after EVT in patients with acute BAO. In particular, patients with good initial collateral status and distal BAO may consider EVT even if the treatment is started beyond appropriate time line. Computed tomographic angiography, acute ischemic stroke, basilar artery occlusion, collateral circulation Disclosures: S. Ha: None.